Publicly Available Pricing Information for Orthopaedic Upper Extremity Procedures in the United States Lacks Transparency and Consistency Between Major Hospitals - M. Lane Moore, B.S; Jordan R. Pollock, B.S; Matthew K. Doan, B.S; Jack M. Haglin, B.S; Kelly L. Scott, M.D., M.P.H; Joshua S. Bingham, M.D; Karan A. Patel, M.D (Elsevier, 2022)
Purpose: The purpose of this study was to assess the price variation of various Medicare severity diagnosis-related group codes for orthopaedic upper extremity procedures for the top 20 orthopaedic hospitals using chargemaster price listings from each hospital. Methods: The top 20 orthopaedic hospitals in the United States were determined by querying the U.S. News and World Report's 2020 orthopaedic hospital ranking. This report ranks orthopaedic hospitals according to 4 major domains: outcomes, structure, process/expert opinion, and patient experience. Chargemaster data for the top 20 orthopaedic hospitals was compiled from their websites. Five DRG codes that represented orthopaedic upper extremity procedures were selected, and the pricing information for each was extracted from hospital chargemasters. The median income and cost-of-living index were also compiled for the county that each hospital is located in so that pricing data could be compared to economic measures through regression analysis. Results: Of the top 20 orthopaedic hospitals, 18 had publicly available pricing information in DRG format on their websites. The DRG code with the highest pricing variability was Hand Injury Procedures (DRG 906; range, $12,832-$253,633). The procedure with the least pricing variability was Hand or Wrist Procedures (DRG 514; range, $24,533-$128,403). Additionally, only the cost of living index was a statistically significant predictor of procedure pricing with a weak correlation. Conclusion: Hospital chargemaster listings are lacking in 2 major areas: true price transparency and standardization/consistency between hospitals. Chargemaster data are often difficult to find, confusing to patients, and inaccurate. Additionally, the price range for a single DRG code can also vary substantially depending on the hospital. It is possible that hospitals located in areas with high costs of living and median incomes would charge higher prices, but these factors were not found to support this hypothesis.